Insecurity, School Administration, Teachers Job Performance and Students Performance in Post-Basic Education and Career Development (PBECD) in Nigeria - Cletus, Ngezack Amos; Mshelie Jonathan Helen; Usi Christiana (International Journal of Law Analytics, 2024)
This paper assessed the impact of insecurity on school administration, teachers’ job performance, and students’ academic performance in Post-Basic Education and Career Development (PBECD) in Nigeria. Secondary data were used in the paper. The data were collected from print and online publications. The paper established that insecurity in Nigeria affected school administration, teachers’ job performance, and students’ academics in Post-Basic Education and Career Development (PBECD) in Nigeria.  Based on these discoveries, the paper hereby recommended that the Nigerian government should develop the political will to fight all forms of insecurity in the country by addressing socio-economic problems causing insecurity across the country. All levels of government should invest in school security by providing security facilities in the schools. The government should employ competent, agile, and well-trained school security guards in all schools.